'Go Crowded' Advertising Strategy: Increase Travel Agency Intent, Recommendations, and Engagement - Osijo, Immanuel Ustradi; Osiyo, Abraham Krishna Martadinata (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Advertisements play an essential role in shaping consumer intentions and engagement, including in the travel agency industry. The "Pergi Rame-Rame" campaign was designed to attract potential customers in Malang by emphasizing the value of togetherness in traveling. This study analyzed the influence of the advertisement on consumer intentions, recommendations, and engagement. A quantitative approach with an experimental survey method was used to measure the impact of the advertisement intervention on dependent variables. Respondents consisted of 320 potential customers who were exposed to the advertisement, and changes in their intentions and engagement with the travel agency were then analyzed. The research findings indicate that culturally relevant and creative ads enhance customer intention, encourage recommendations, and strengthen their engagement with the travel agency. Before the intervention, there was no significant difference between the two groups; however, after the intervention, the group exposed to Digital Content Marketing showed a significant increase in intention, recommendation, and engagement compared to the control group. These findings highlight the need for travel agencies to develop culturally relevant marketing strategies that are more informative and visually appealing to attract more customers. Including customer testimonials and interactive promotions can enhance advertisement appeal. This study contributes to understanding the effectiveness of hyper-local advertisements in influencing consumer behavior and provides insights for developing more strategic and socially driven marketing campaigns. Iklan berperan penting dalam membentuk niat dan keterlibatan konsumen, termasuk dalam industri biro perjalanan. Kampanye "Pergi Rame-Rame" dirancang untuk menarik minat calon pelanggan di Malang dengan menekankan nilai kebersamaan dalam bepergian. Penelitian ini menganalisis pengaruh iklan terhadap niat, rekomendasi, dan keterlibatan calon konsumen. Pendekatan kuantitatif dengan metode survei eksperimental digunakan untuk mengukur dampak intervensi iklan terhadap variabel dependen. Responden terdiri dari 320 calon pelanggan yang diberikan paparan iklan, kemudian dianalisis perubahan dalam niat dan keterlibatan mereka terhadap biro perjalanan. Hasil penelitian menunjukkan bahwa iklan kreatif dan relevan secara budaya meningkatkan niat pelanggan, mendorong rekomendasi, dan memperkuat keterlibatan mereka dengan biro perjalanan. sebelum intervensi tidak ada perbedaan signifikan antara kedua kelompok, namun setelah intervensi, kelompok yang diberi Digital Content Marketing menunjukkan peningkatan signifikan dalam intention, recommendation, dan engagement dibandingkan dengan kelompok kontrol. Implikasi temuan ini menegaskan bahwa biro perjalanan perlu menyusun strategi pemasaran berbasis budaya yang lebih informatif dan menarik secara visual untuk menarik lebih banyak pelanggan. Menyertakan testimoni pelanggan dan promosi interaktif dapat memperkuat daya tarik iklan. Penelitian ini berkontribusi pada pemahaman efektivitas iklan hiper-lokal dalam memengaruhi perilaku konsumen serta memberikan wawasan bagi pengembangan kampanye pemasaran yang lebih strategis dan berbasis nilai sosial.